Immune response to Streptococcus pneumoniae in asthma patients: comparison between stable situation and exacerbation. (6th June 2013) - Otero, C.; Paz, R. D.; Galassi, N.; Bezrodnik, L.; Finiasz, M. R.; Fink, S.
Summary In Argentina, more than 3 million people suffer from asthma, with numbers rising. When asthma patients acquire viral infections which, in turn, trigger the asthmatic response, they may develop subsequent bacterial infections, mainly by Streptococcus (S.) pneumoniae. This encapsulated Gram+ bacterium has been considered historically a T cell‐independent antigen. Nevertheless, several papers describe the role of T cells in the immune response to S. pneumoniae. We evaluated the response to S. pneumoniae and compared it to the response to Mycobacterium (M.) tuberculosis, a different type of bacterium that requires a T helper type 1 (Th1) response, in cells from atopic asthmatic children, to compare parameters for the same individual under exacerbation and in a stable situation whenever possible. We studied asthma patients and a control group of age‐matched children, evaluating cell populations, activation markers and cytokine production by flow cytometry, and cytokine concentration in serum and cell culture supernatants by enzyme‐linked immunosorbent assay (ELISA). No differences were observed in γδ T cells for the same patient in either situation, and a tendency to lower percentages of CD4+CD25hi T cells was observed under stability. A significantly lower production of tumour necrosis factor (TNF)‐α and a significantly higher production of interleukin (IL)‐5 was observed in asthma patients compared to healthy individuals, but no differences could be observed for IL‐4, IL‐13 or IL‐10. A greater early activation response against M. tuberculosis, compared to S. pneumoniae, was observed in the asthmatic patients' cells. This may contribute to explaining why these patients frequently acquire infections caused by the latter bacterium and not the former.